Effects of Climate Change on Crop Yield: Is it a Benefit or Menace? - Odeyomi, Omowunmi A.; Ejimakor, Godfrey; Isikhuemhen, Omoanghe S. (European Scientific Journal, ESJ, 2024)
The review explained the detrimental and beneficial effects of climate change on crop yields of major value crops such as corn, wheat, rice, and soybean. The trend in crop yields of these crops among the largest food producers in the world was examined. The study observed the changes that have occurred in crop yields because of climate change over the years. The changes have effects that cause shifts in temperature and precipitation, rising sea levels, and loss of biodiversity which are detrimental to the environment, economy, and health of humans, plants and animals, and the ecosystem in general. The effects of these changes as observed in plants cause high CO2 levels, increased temperature and precipitation, droughts, floods pests, and diseases. The study emphasized the fact that some phenomena caused by climate change such as CO2 fertilization and increased temperature because of global warming proved to be beneficial to crop yields in specific crops. Further deliberations on the effects on yields looked into the implications of factors such as weather, crop physiology, soil properties, and the economic aspect of how climate change affected the yield of crops. We then emphasized the fact that adaptation and mitigation strategies should be put in place to reduce the effects of climate change on the yield of crops by taking into consideration the beneficial aspects and non-beneficial aspects of climate change.